Building National Character Through Social Studies Based on Society 4.0 Values Post-Pandemic COVID-19 - Ruhimat, Mamat; Logayah, Dina Siti; Arrasyid, Riko (KnE Social Sciences, 2024)
This paper’s fundamental problem is building national character through social studies based on Society 4.0 in the post-COVID-19 pandemic. This is because the learning process during the COVID-19 pandemic takes place online using a platform to support learning. The use of the platform is a problem that has not been touched on, namely, the formation of student character. This study uses a qualitative approach to produce an overview of social studies learning methods based on the national character to improve teacher professional competence. A total of 35 social studies teachers were taken as samples. The results obtained in this study, namely the solution in the form of developing learning methods that tend to be monotonous, which so far have been carried out, must be combined with methods that provide more space for students to develop their potential. In this connection, national character is interpreted as a way of thinking and behaving that shows the differences of everyone to live and work together for a better life for society and the nation. The 2013 curriculum on social studies subjects was developed as an integrative social studies subject, not as separate disciplines. Social studies subjects are, of course, applicative-oriented education, as the development of inquiry abilities, learning abilities, and character education such as curiosity, creativity, honesty, and the development of a caring and responsible attitude towards the surrounding environment and social relations. Keywords: building national character, social studies learning, community values 4.0